P3SPS pada Program Talk Show Mata Najwa Episode PSSI Bisa Apa Jilid 6: Lagi-Lagi Begini - Anggraini, Ayu Dwi; Hartanto, Denny Antyo; Kartika, Bambang Aris (Universitas Jember, 2024)
Television has a significant influence in shaping public opinion and mindset. Research in 2021 found some programs didn't meet KPI standards.